Sex-specific effects of prenatal bisphenol A exposure on transcriptome-interactome profiles of autism candidate genes in neural stem cells from offspring hippocampus - Kasidit Kasitipradit; Surangrat Thongkorn; Songphon Kanlayaprasit; Thanit Saeliw; Pattanachat Lertpeerapan; Pawinee Panjabud; Depicha Jindatip; Valerie W. Hu; Takako Kikkawa; Noriko Osumi; Tewarit Sarachana (Scientific Reports)
Abstract Bisphenol A (BPA), an endocrine-disrupting chemical, is increasingly linked to the pathogenesis of autism spectrum disorder (ASD). This study investigates the effects of prenatal BPA exposure on neural stem cells (NSCs) from the hippocampi of rat offspring, a brain region critical for neurodevelopment and implicated in ASD. Pregnant rats were administered with BPA or vehicle control once daily via oral gavage from gestational day 1 until parturition. NSCs were isolated from the offspring’s hippocampi on postnatal day 1, and RNA sequencing was performed to examine transcriptomic alterations. Differentially expressed genes (DEGs) were identified through RNA-seq and further analyzed using Ingenuity Pathway Analysis (IPA) to explore disrupted pathways. In addition, in vitro proliferation assays were conducted, utilizing immunofluorescence staining for Sox2, a stem cell marker, and BrdU to quantify proliferating NSCs. Our results revealed that prenatal BPA exposure induced sex-specific alterations in NSC gene expression, with ASD-related genes such as Atp1a3, Nefl, and Grin1 being particularly dysregulated in male offspring. Moreover, sex-specific changes in NSC proliferation were observed. The study underscores BPA’s potential as an environmental risk factor for ASD, emphasizing the need for further research into its role in sex-specific neurodevelopmental effects.